A Soil moisture sensor based on Internet of Things LoRa - adi, Puput Dani Prasetyo; siregar, Victor M.M. (Internet of Things and Artificial Intelligence Journal, 2021)
This study discusses the Performance of Moisture soil sensor, which is useful as a sensor to detect soil moisture level used as plant nutrition. The monitoring process is carried out in real-time using internet of things technology based on LoRa or Long-Range Radio Frequency (IoT-LoRa). The application server used is Thingspeak. With this research, agricultural processes and monitoring can be carried out dynamically and efficiently. Therefore, when the soil conditions are dry or the soil moisture level is <300, it will immediately affect automatic watering by opening the valve or rotating the Servo motor. Furthermore, the watering process can be done automatically by looking at the soil conditions on potted plants or agricultural land. The position of the sensor on the ground level is not immediately removed and moved to another place, but it is always in the same condition and location, so the Adaptive Data Rate mechanism is used for the management of Power Consumption on IoT-LoRa